PERAN ORANG TUA DALAM PEMBELAJARAN DARING (DALAM JARINGAN) SELAMA MASA PANDEMI COVID-19 DI SDN 2 SUMBERSUKO KECAMATAN DAMPIT KABUPATEN MALANG - Zilda Ba’da Mawlyda Iliyyun1; Rosichin Mansur; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This research aims to see how the implementation of online learning, the role of parents in online learning as well as the supporting and inhibiting factors experienced by parents in online learning during the covid-19 pandemic at SDN 2 Sumbersuko Kecamatan Dampit Kabupaten Malang. In this pandemic condition, it is parents who have a big influence on online learning that is done at home. Sources of data obtained from the principal, homeroom teacher, and parents of students. This study uses a qualitative method with the types of cases a research study, where data were obtained based on observations, interviews and documentation, analyzed with data condensation, data dispalay and making conclusions and verification. The results of this study indicate that parents have a very important role in this online learning Keywords: parents, online learning, covid-19This research aims to see how the implementation of online learning, the role of parents in online learning as well as the supporting and inhibiting factors experienced by parents in online learning during the covid-19 pandemic at SDN 2 Sumbersuko Kecamatan Dampit Kabupaten Malang. In this pandemic condition, it is parents who have a big influence on online learning that is done at home. Sources of data obtained from the principal, homeroom teacher, and parents of students. This study uses a qualitative method with the types of cases a research study, where data were obtained based on observations, interviews and documentation, analyzed with data condensation, data dispalay and making conclusions and verification. The results of this study indicate that parents have a very important role in this online learning. Keywords: parents, online learning, covid-19